Analytical Determination of Heat State Indices of Stacks with Pressing Lining - I. I. Strikha (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A methodology for heat calculation of stacks with pressing lining in order to determine indices of temperature state of the lining and bearing shaft during shut-downs, starts and also stationary conditions is presented in the paper. The paper contains results of test calculations for stacks with the purpose to prevent crack-formation at their separate zones along the height and ensure their reliable operation.